Gibt es einen Einfluss emotionaler Gesichter auf basale Quantifizierungsprozesse? : Untersuchung einer potentiellen Methode zur diagnostischen Eingrenzung und Früherkennung der Borderline-Persönlichkeitsstörung - Kühner, Eva Katharina; Justus Liebig University Giessen (My University, 2014)
Gesichtererkennung und Emotionsverarbeitung spielen in der Kognitionsforschung eine wichtige Rolle. Ziel der vorliegenden Arbeit war es, herauszufinden, ob es einen Einfluss emotionaler Gesichter auf basale Quantifizierungsprozesse gibt, mit dem Hintergrund eine potentielle Methode zur diagnostischen Eingrenzung und Früherkennung der Borderline-Persönlichkeitsstörung (BPS) zu untersuchen. An einer Stichprobe gesunder Probanden sollten die potentiell relevanten Einflussgrößen auf die Untersuchungsmethode ermittelt werden. Das Probandenkollektiv setzte sich aus zehn männlichen und zehn weiblichen Studenten zusammen, die im Durchschnitt 24,6 Jahre alt waren.Vor allem das verstärkte und schnellere Erkennen und Auffinden von ärgerlichen Gesichtern in einer Menge Gesichter mit anderem Gesichtsausdruck, auch als anger-superiority Effekt (ASE) bezeichnet, steht in der Diskussion im Zusammenhang mit dem sogenannten negativen Bias , der negativeren Bewertung neutraler oder ambivalenter Emotionen, bei Patienten, die an BPS erkrankt sind. Allerdings ist man sich in der Fachwelt nicht einig, ob ein ASE überhaupt existiert und unter welchen Umständen er auftritt. Zahlreiche Autoren konnten den Nachweis für einen ASE erbringen, andere jedoch wiesen in ihren Untersuchungen genau das Gegenteil nach und propagieren einen happy-superiority Effekt (HSE). In der vorliegenden Arbeit wurde der ASE erneut im Rahmen einer visuellen Suchaufgabe in Form eines Finding-the-face-in-the-crowd (FFIC) Paradigmas überprüft. Unter den gewählten Bedingungen trat kein ASE auf.Auf der Basis des ersten Experiments wurde ein zweites generiert. Dabei wurden die basalen Quantifizierungsprozesse Subitizing und Counting untersucht. Als Subitizing werden die Verarbeitungsprozesse im Gehirn beim Erfassen kleiner Elementanzahlen, von 1-3 oder 1-4 Elementen, je nach Autor, bezeichnet. Counting beschreibt den Prozess des Abzählens größerer Elementanzahlen, je nach Autor von 4-7 oder 5-7 Elementen (Mandler & Shebo, 1982). Mit dem Ziel herauszufinden, wie sich emotionale Gesichter auf diese Quantifizierungsprozesse auswirken, wurde eine Quantifizierungsaufgabe entwickelt, im Rahmen derer Gesichter gezählt und mit einer Zahl verglichen werden sollten. Es wurden die gleichen schematischen emotionalen Gesichter und schematischen Figuren in der Kontrollbedingung verwendet wie im FFIC Paradigma. Gemessen und ausgewertet wurde die Reaktionszeit. Dabei konnte nachgewiesen werden, dass die emotionalen Gesichter die Prozesse des Subitizing nicht beeinflussten. Im Counting Bereich hingegen führten die emotionalen Gesichter zu verlängerten Reaktionszeiten und störten die Verarbeitung somit nachweislich. Eine Sonderstellung der Emotionsqualität Ärger im Hinblick auf den negativen Bias konnte nicht gefunden werden.Anhand dieser Ergebnisse wurden schließlich die möglichen Aspekte und Einflüsse der Emotionsverarbeitung und Gesichtererkennung auf die Quantifizierungsprozesse sowie alternative Lösungs- und Erklärungsansätze aufgezeigt und diskutiert. Es wurde zudem darauf verwiesen, dass weitere Untersuchungen mit einem klinischen Probandenkollektiv an BPS erkrankter Patienten verschiedener Modifikationen, wie einer Kürzung der Untersuchungsdauer, bedürften.

Emotion recognition and the processing of facial expressions play an important role in neuroscience and cognition research. Especially the fast and accurate recognition of angry faces is discussed controversially. To this day there is no agreement about the question if there is a so called anger-superiority effect (ASE) and under which conditions it appears.On one hand there are studies that show this effect as a preattentive and automatic process of emotion recognition. On the other hand there are results that confirm the opinion that the ASE exists, but that it isn t characterized by a preattentive kind of processing and that angry faces are only found a little faster than other types of facial expressions. An also existing different view is that there is no ASE but a so called happy-superiority effect (HSE) with the preference and the faster finding of happy faces compared to other facial expressions.A scientific paradigm to investigate this phenomenon is the finding-the-face-in-the-crowd (FFIC) paradigm. The participants job is to find emotional facial expressions in a crowd of neutral and/or different emotional facial expressions. The reaction time is determined meanwhile. In the present study we investigated how the processing of emotional faces affects other cognitive processes. Especially the determination of numbers hasn t yet been examined. If there is an impact of emotional faces on other cognitive processes, this could be of great importance in particular for the clinical medical sector. There are some psychiatric diseases which could occur linked to such an effect. There is the presumption that e.g. depressions and the borderline-personality disorder come along with the preferred negative perception of situations and interpersonal contacts. This so called negative bias could possibly be detected by the finding of an ASE. The impact of such an ASE on other cognitive processes could affect the whole interpersonal interactions and the actions of such patients in general. In this survey we were testing the hypothesis that there is an ASE and that this ASE would have a direct impact on the basal counting processes of subitizing and counting . Subitizing is a phenomenon which describes the fast and accurate, preattentive and automatic registration of a number up to three or four objects in parallel. Counting describes the registration of numbers larger than four objects. Therefore a computer simulation program named Presentation was used to present displays with varying tasks. For the appliance the participants used a tablet with an electronic pen. The participants who took part were all healthy students, 10 female und 10 male ones.At first a classical FFIC paradigm was used to detect whether there is an ASE or not. In the next step we presented a certain amount of faces that should be counted. The numbers varied from one to eight faces in one display. The participants of the experiments had to decide if the shown number was equal to a written digit on the bottom of the display. In some trials there were emotional faces of the emotions happy or angry between the neutral, non-emotional faces. The sequence of the trials in one test series changed from participant to participant. It was tested if the reaction time to determine the face number increased in the cases of the appearance of the emotional distractor faces. The results showed that there was no ASE and that emotional faces had no impact on the process of subitizing but that they had a significant impact on the process of counting with the increase of the reaction times. In case of the emotional quality of the facial expression there was no significant difference between angry and happy faces. These results have been discussed referring to their meaning for the clinical medical background and the neuroscientific point of view in general. Possible and reasonable verifications and modifications as well as expansion of the experiment and its design were presented and discussed.
Keywords: Emotionserkennung; Quantifizierung; Subitizing; Counting; Emotion recognition; Subitizing; Counting; ddc:610